The kingdom with no stories - Ordinario, Mary Ann (ABC Educational Development Center Children's Books, Inc., 2007)
Long ago, there lived a king who hated stories. He believes that writing and reading stories will not help his kingdom to prosper. But there was a humble lady named Rainmari who could not accept this rule. She secretly wrote her stories at night and kept it inside her huge rag doll. What will happen when the king learns about her secret?--Back cover.